The ammonoid fauna of the Prionocyclus germari Zone (upper Turonian, upper Cretaceous) from Rochefort-en-Valdaine (Drôme, France) - Baudouin, Cyril; Delanoy, Gérard; Ifrim, Christina; Moreno-Bedmar, Josep Anton (Carnets de géologie, 2018)
The late Turonian ammonoid fauna of Rochefort-en-Valdaine (Drôme, France) is herein described in detail and the intraspecific variability of Vocontiiceras vocontiense Diebold et al., 2018, is studied. The ammonoid assemblage (9 taxa identified) was deposited within the Prionocyclus germari Zone, which was defined in Germany, and is now also documented in southeastern France. Moreover, the co-occurrence of the heteromorph ammonoids Hyphantoceras (Hyphantoceras) flexuosum (Schlüter) and Hyphantoceras (Hyphantoceras) ernsti Wiese indicates the lower part of the Prionocyclus germari Zone.
Gesehen am 05.03.2020